Company merger in Algeria: A reading of Legal and Aaccounting Rules - بودربالة سارة حدة (Milev Journal of Research and Studies, 2020)
The purpose of this article is to study the legal and accounting rules of corporate merger stipulated by Algerian legislature, since the legal aspect of merger is the legal procedure of accounting, by determining the legal consequences of the merger, such as the disappearance of the legal personality of company, and making contribution of its assets to existing companies (capital increase) or participate in the constitution of a new company. The study reached a number of conclusions, the most important was the lack of a definition of the concept of corporate merger in Algerian legislation and recommended that these gaps be filled by the legislator.